When BDI Meets Argumentation: The Conceptual Ideal - Cheah, Wai Shiang; Kulathuramaiyer, Narayanan; Lai, Suk Fui (IEEE, 2006)
Argument-based negotiation consists of a meaningful expression, able to provide better reasoning features and flexibility. Agents in this case, become aware of the information surrounding them in an attempt to analyze, influence and understand its counterparts or opponents. The agents behave intelligently to facilitate the argumentation process, which consists of argument interpretation, argument evaluation, argument generation and argument selection. The Belief, Desire, Intention (BDI) mode, on the other hand, is a widely adopted for modeling intelligence. Hence, we explore the relationship between these two models. We argue that a typical intelligent model involves two component, which are the reasoning and communication components. The integration between these components, however, is still unclear. This paper proposes the integration among the reasoning aspect (BDI in particular) and communication aspect (argumentation specifically) in an open multi-agent society. The capability of argument-based negotiation enables the BDI agent in intention reconsideration, to enhance its reasoning powers.